Direct analysis of cotton swipes for plutonium isotope determination by microextraction-ICP-MS. Issue 10 (16th September 2021) - Manard, Benjamin T.; Metzger, Shalina C.; Rogers, Kayron T.; Ticknor, Brian W.; Zirakparvar, N. Alex; Roach, Benjamin D.; Bostick, Debra A.; Hexel, Cole R.
Abstract : This study demonstrates a method for determining the isotopic composition of low-level (sub-pg) plutonium (Pu) directly from a cotton swipe. Abstract : This study demonstrates a method for determining the isotopic composition of low-level (sub-pg) plutonium (Pu) directly from a cotton swipe. Environmental sample (ES) swipes are routinely employed as a tool for monitoring activities in nuclear facilities. Traditional ES swipe analysis, as employed in nuclear safeguards, utilizes laborious ashing, digestion, and chemical separation procedures prior to mass spectrometric (MS) analysis. Here, an innovative sample introduction technique employing a microextraction probe to extract Pu directly from the swipe surface is described. The microextraction probe lowers onto the swipe surface, seals on a small area (8 mm 2 ), and delivers solvent (2% HNO3 ) to extract actinide material that may be present. The extracted analyte is subsequently directed into a sector field inductively coupled plasma (ICP)-MS for isotope ratio determination. This microextraction-ICP-MS method successfully determined the isotopic composition ( 240 Pu/ 239 Pu and 242 Pu/ 239 Pu) of three Pu certified reference materials (CRM 136, 137, and 138) that were deposited (1 pg) onto ES swipes. The percent relative difference from the certified value, uncorrected for instrumental fractionation, was <2% for the 240 Pu/ 239 Pu ratio on all three CRMs and <10% for the 242 Pu/ 239 Pu ratio on CRM 136 and 138. The percent relative standard deviation, an estimate of the sample-to-sample isotopic precision, was <4% for the 240 Pu/ 239 Pu and <15% for the 242 Pu/ 239 Pu. Method limits of detection were determined, based on measurements of an enriched 244 Pu material, to be ∼7 fg. Additionally, a mixed uranium (U) and Pu deposition was made to determine the method's ability to simultaneously extract U and Pu and determine the isotopic composition of both analytes.